Borderline ovarian tumor in women aged ≥65 years: impact on recurrence and survival. (January 2015) - Song, Taejong; Lee, Yoo-Young; Choi, Chel Hun; Kim, Tae-Joong; Lee, Jeong-Won; Bae, Duk-Soo; Kim, Byoung-Gie
Abstract: Objective : Borderline ovarian tumor (BOT) is uncommon in women with advanced age. The authors investigated the characteristics and treatment outcomes of women with BOT ≥65 years of age. Study Design : A hospital-based tumor registry was used to identify retrospectively patients with BOT who were treated between 1996 and 2011. Patients were divided into two cohorts: women aged <65 years and women aged ≥65 years. Recurrence and survival was examined using the Kaplan–Meier method. Multivariate Cox proportional hazards model was used to estimate hazard ratios with 95% confidence intervals (95% CI). Results : In total, 364 patients were identified, including 326 patients aged <65 years and 38 patients aged ≥65 years. The elderly patients had more comorbidities ( P < 0.001), larger tumor size at diagnosis ( P = 0.001), more perioperative complications ( P = 0.001), and longer postoperative hospital stay ( P < 0.001). In a multivariate model, the hazard ratios for recurrence and disease-related death in patients aged ≥65 years were 2.53 (95% CI, 1.03–6.23) and 7.66 (95% CI, 1.09–53.95), respectively. Conclusions : Characteristics and survival of patients with BOTs aged ≥65 years differ distinctly from those of patients aged <65 years. Old age was an independent poor prognostic factor of recurrence and disease-related death.